Stereocontrolled Synthesis of 2S,3R-(3)-Piperidinyl Glycine and 2S,4S-(3)-Piperidinyl Alanine: Medicinally Relevant Constrained Cyclic Amino Acids - Hocine, Sofiane; Skrzypczak, Paul; Cosson, Victor; Boudjerada, Nazim; Hanessian, Stephen (Synthesis, 2025)
The stereocontrolled syntheses of 2S,3R-(3)-piperidinyl glycine hydrochloride and 2S,4S-(3)-piperidinyl alanine hydrochloride are described. These conformationally constrained α,γ- and α,δ-diamino acids were obtained via the stereoselective allylation of N–Cbz aspartate and glutamate diesters, respectively, followed by the intramolecular cyclization to form the piperidine ring. Orthogonally protected intermediates enabled late-stage diversification. Final deprotections afforded the target amino acids in high yields. The combination of the natural α-amino acid fragment and the basic piperidine unit in 3-piperidinyl glycine and alanine reveals the embedded frameworks of l-ornithine and l-lysine, making them peripheral or inserted components within structures of bioactive compounds of value for drug optimization and development.
Keywords: Ring constrain; Unnatural amino acid; Asymmetric amino acids synthesis